The Role of Emotion Regulation in the Vicarious Trauma Risk Reduction among Psychotherapists - Meloian, Anait; Likarchuk, Yevhen; Svіdenska, Halyna; Kiian, Andrii; Makarenko, Svitlana (International Journal of Statistics in Medical Research, 2025)
The relevance of the study is determined by the increasing risk of vicarious trauma among psychotherapists because of their high emotional and professional stress. The study explores the link between emotion regulation training and vicarious trauma risk, well-being, and professional functioning in psychotherapists. The study employed the methods of testing and questionnaire survey (Emotion Regulation Questionnaire (ERQ), Perceived Stress Scale (PSS), and Professional Quality of Life Scale (ProQOL)). The following statistical methods were also used: descriptive statistics, Shapiro-Wilk test, paired t-test, Wilcoxon test, effect coefficients, multiple regression analysis, 95% confidence intervals. The reliability of the instruments was tested using Cronbach α. The intervention was associated with improvements in emotion regulation, stress reduction, and vicarious trauma symptoms (all p < 0.001). However, the absence of a control group precludes definitive causal attributions, as changes may reflect external factors (e.g., natural recovery, concurrent supervision). Despite this limitation, effect sizes (Cohen’s d = 0.55–0.70) and 12-month stability suggest clinical promise warranting future RCTs. Changes remained stable over the year, but some indicators showed partial regression. The women demonstrated higher levels of well-being, while gender differences on other parameters were minimal (p = 0.041). Furthermore, findings are contextually bound to urban psychotherapists in Kyiv due to purposive sampling; generalizability to rural settings or distinct healthcare systems requires verification.